Contributions to an Economic History of the Present Time: The 2007/2008 Crisis as a Structuring Historical Event (Ágora Journal, 2026)
Abstract: This article proposes an analysis of the 2007/2008 Financial Crisis as a structuring historical event of the present time, whose magnitude and lasting effects challenge traditional approaches in economic history. Drawing on Contemporary History as a methodological field, the study explores how the crisis, which began in the U.S. and spread globally, exposed the limits of the neoliberal financialized regime and triggered transformations in regulation, governance, and social organization. The research is divided into two sections: the first addresses the epistemological foundations of HTP and its dialogue with economic history; the second analyzes the crisis itself, its causes, and its impacts in the U.S. and Brazil. By linking structure and event, memory and politics, the approach seeks to critically understand institutional shifts and the new regime of historicity in contemporary capitalism, demonstrating how HTP contributes to analyzing events still under semantic and political dispute.
Keywords: Economic History; Contemporany History, 2007/2008 Financial Crisis; Neoliberal Capitalism